2019
DOI: 10.1038/s41598-019-39474-x
|View full text |Cite
|
Sign up to set email alerts
|

Sub-seasonal Levee Deformation Observed Using Satellite Radar Interferometry to Enhance Flood Protection

Abstract: Levees are critical in providing protection against catastrophic flood events, and thus require continuous monitoring. Current levee inspection methods rely on limited information obtained by visual inspection, resulting in infrequent, localized, mostly qualitative and subjective assessments. This hampers the timely detection of problematic locations and the assessment of levee safety in general. Satellite radar interferometry yields weekly observations of levee conditions with high precision which complement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The great reduction of the emerged surfaces and coastal elements could represent a serious problem in the study area: these portions are essential for the protection of the earthen levees from the erosive action by the sea waves motion; the disappearance of these elements exposes the defense infrastructures to the risk of breaks and/or collapses [56]. In addition, the reduction of the safety margin between the mean sea level and the top of the levees, in the order of 3-4 m at present day, will increase the frequency and extent of flooding and, in general, the overall hydraulic risk of the area.…”
Section: Discussionmentioning
confidence: 99%
“…The great reduction of the emerged surfaces and coastal elements could represent a serious problem in the study area: these portions are essential for the protection of the earthen levees from the erosive action by the sea waves motion; the disappearance of these elements exposes the defense infrastructures to the risk of breaks and/or collapses [56]. In addition, the reduction of the safety margin between the mean sea level and the top of the levees, in the order of 3-4 m at present day, will increase the frequency and extent of flooding and, in general, the overall hydraulic risk of the area.…”
Section: Discussionmentioning
confidence: 99%
“…Surface characteristics (soil, soil moisture, and vegetation) can also cause phase disturbances in the InSAR signal. Studies that observed this seasonal noise, often up to approximately 1 cm [10,11,[19][20][21][22], base their explanations on statistical correlation with other seasonal patterns, such as swelling and shrinking of clay, changes in groundwater level, or crop and soil moisture.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a set of co-registered radar acquisitions, coherent scatterers are identified and their deformation time series are estimated [3][4][5][6]. Several studies have shown the potential of MT-InSAR for the observation of (line-)infrastructure, such as dams, dikes, tunnels, roads, highways and railways [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…To estimate and distinguish different deformation regimes, a proper parameterization of the deformation is required. For example, previous research has shown that temperature [28], possibly in combination with rainfall [7], is a good proxy for sub-seasonal deformation assessment. This applies both for concrete/metal constructions, as well as for embankments.…”
Section: Introductionmentioning
confidence: 99%